CHARACTER EDUCATION AT MA DARUL IKHLAS PANYABUNGAN - Siti Mutiah; Ardila Syafitri; Tiara Syahputri Gumanti (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to determine the role and responsibilities of teachers in implementing character building in Madrasah Aliyah Darul Ikhlas Panyabungan. This study is a field research (field research) using descriptive qualitative approach. The population consisted of all teachers Madrasah Aliyah Darul Ikhlas Panyabungan 30 people, and the sample 57 teachers in class XII. Methods of data collection in this study used the method of observation, interviews and documentation. The research result is the existence of insufficient learning facilities, extra-curricular activities. The participation of teachers in routine activities is required such as the implementation of the prayers in the mosque and spontaneous activities, such as giving sanction to students who are late, make slogans that can affect students for good character. Character education is defined as moral education, character values, moral education and character education which has the aim of developing a person's ability to be able to make good and bad decisions, realizing a share in all aspects of life. Therefore, character education will be carried out if it is in line with the right education system and with superior educators.Keywords: - Character education, moral crisis, task of the teacher